Statistical governance and FDI in emerging economies - Ulf von Kalckreuth (Deutsche Bundesbank, 2019)
The importance of institutional settings for economic development outcomes is broadly acknowledged nowadays. This paper investigates the role of official statistics in alleviating financing constraints in emerging and developing economies, with a particular focus on Sub-Saharan Africa. Official statistics has a major dual role: it directly adds to the information set of investors regarding the general state of the economy and it is a key commitment and signalling device as to future good governance. Empirically, the paper investigates, for a sample of 98 emerging and developing countries, the relationship between the adoption of the IMF General Data Dissemination Standard (GDDS) for statistical data production and the net incurrence of foreign direct investment liabilities. Direct investment is considerably higher under GDDS. Controlling also for time and country effects, using fixed effects and quantile panel regression, the relationship ceases to be uniformly positive. Heterogeneity matters: There is a large and significant difference between poorer and richer countries, as well as between countries in Sub-Saharan Africa and elsewhere. Given the information asymmetry problems in poor developing countries, this is not unexpected. Furthermore, it becomes evident that the relationship between the adoption of GDDS and net incurrence of FDI liabilities is negative for richer countries and outside Sub-Saharan Africa. For richer countries, the relevant alternative might have been the more demanding SDDS, turning the adoption of GDDS into an unfavourable signal. Quantile regression is carried out using the quantile panel estimator of Canay (2011).
Keywords: O16; G31; D82; 330; governance; FDI; emerging economies; policy evaluation; quantile panel regression; Compact with Africa; official statistics; asymmetric information; financing constraints